Gini impurity based NDN cache pollution attack defence mechanism. Issue 6 (17th August 2020) - Singh, Vishwa Pratap; Ujjwal, R. L.
Abstract: Name Data Network (NDN) is a futuristic Internet architecture that delivers content based on strategically chosen names and caches content on intermediate routers in the content-delivery path, which is used to fulfill future requests for the same data. In-network caching significantly improves network throughput but also makes NDN vulnerable to revamp security attacks such as cache poisoning, cache pollution, and cache snooping. In this paper, we focused on content pollution attack, in which the attacker disrupts the cache locality by intelligently crafted fake requests. This paper introduce monitor metrics for quantitative anomaly detection of requests and proposed a scheme based on Gini Impurity to detect network under cache pollution attack. The paper also proposed an Interest throttling mechanism based on trust to reinforce network under cache pollution attacks. The proposed scheme is evaluated through various experiments on NdnSIM simulator.